The Students’ Response Analysis of English for Specific Purposes Speaking Class through Role Play (Job Interview) of Economics Students in Semarang University - Dini Anggraheni Dini Anggraheni (Universitas PGRI Semarang, 2018)
The purpose of this study was to analyze the students’ response of English for Specific Purposes (ESP) speaking class through role play (job interview) of economics students in Semarang University. The writer uses questionnaires to analyze the students’ response and Likerts scale to count and also describe the students’ response. The result of this study came from 2 statements in questionnaires that chosen by 40 students. It shows 77 % for first statement and 75% for second statements. The result tells that the students agree with the role play (simulation) method for job interview that practiced in ESP speaking class. It also shows that the students feel that role play can make it easier to learn English especially in speaking.